Фінансові ресурси електротранспортних підприємств - Петрук, О. М.; Трусова, Наталя Вікторівна; Трусова, Наталья Викторовна; Trusova, Natalia; Полчанов, А. Ю.; Довгалюк, В. В. (My University, 2021)
UK: У статті розглядаються питання фінансових ресурсів підприємств електротранспорту. Метою статті є визначення ролі фінансових ресурсів та перспективних напрямків фінансового розвитку підприємств електротранспорту, що займаються пасажирськими перевезеннями. Методологічною основою статті стали загальні та спеціальні методи дослідження, зокрема методи теоретичного узагальнення, аналізу, синтезу, а також економіко-статистичні методи. Інформаційною базою дослідження були дані корпорації «Укрелектротранс» про основні показники діяльності міських підприємств електротранспорту України, знос рухомого складу підприємств електротранспорту, а також динаміку доходів та витрат підприємств електротранспорту. Дослідження показує, що витрати підприємств перевищують доходи, а низький рівень доходів від продажу квитків вимагає перегляду тарифного регулювання на державному рівні, що дозволить підприємствам електротранспорту досягти точки беззбитковості. Розрахунки авторів показують, що знос рухомого складу тролейбусів становить 70%, а трамваїв - 92%. Автори пропонують використовувати лізинг як фінансовий інструмент за відсутності інвестиційних джерел, запустити механізми державно-приватного партнерства через концесійну угоду, а також вдосконалити управління фінансами в державних та комунальних підприємствах. Також у статті пропонується поступово замінювати приватний автотранспорт на електротранспорт, що суттєво збільшить пасажиропотік та доходи електротранспортних компаній та поповнить місцевий бюджет, а не бюджет приватних перевізників. EN: The article examines the issues of financial resources of electric transport enterprises. The purpose of the article is to determine the role of financial resources and promising areas of financial development of electric transport enterprises engaged in passenger transportation. The methodological basis of the paper was general and special research methods, in particular methods of theoretical generalization, analysis, synthesis, as well as economic and statistical methods. The information base of the study was Ukrelectrotrans Corporation’s data on main performance indicators of urban electric transport enterprises of Ukraine, deterioration of rolling stock of electric transport enterprises, as well as dynamics of income and expenses of electric transport enterprises. The research shows that the costs of enterprises outweigh the revenues, and the low level of revenues from ticket sales requires a revision of tariff regulation at the state level, which will allow electric transport businesses to reach a break-even point. Authors’ calculations show that the wear of rolling stock of trolleybuses is 70%, and trams are 92%. It has been determined that the unprofitable activity of electric transport enterprises has led to negative consequences such as lack of financial support for renewal and overhaul of rolling stock, low level of activity in attracting international sources of funding, low level of implementation of innovation processes and modernization, inefficient financial management of communal property enterprises, lack of consideration of the cost of transportation when determining fares and low level of attractiveness of the electric transport company for investors due to unprofitable activities. Authors suggest to use of leasing as a financial instrument in the absence of investment sources, launch public-private partnership mechanisms through a concession agreement, as well as improve financial management in public enterprises. Also, in the article proposes to gradually replace private vehicles with electric vehicles, which will significantly increase passenger traffic and revenues of electric transport companies and replenish the local budget, rather than the budget of private carriers.
Financial resources of electric transport enterprises
Keywords: витрати; фінанси; фінансові ресурси; громадський транспорт; доходи; транспортні підприємства; costs; finance; financial resources; public transport; revenues; transport enterprises